Effectiveness of Probiotics in the Prophylaxis of Necrotizing Enterocolitis in Preterm Neonates: A Systematic Review and Meta-analysis - Wanderley Marques Bernardo; Felipe Toyama Aires; Renata Mota Carneiro; Fernando Pereira de Sá; Vera Esteves Vagnozzi Rullo; Dennis Alexander Burns (Jornal de Pediatria, 2013)
Objective: To elucidate the benefits of using probiotics in the prevention of necrotizing enterocolitis (NEC) and its complications in preterm newborns. Method: This was a systematic review of randomized controlled trials, which included studies retrieved from three databases (MEDLINE, Embase, and LILACS), using a combination of the terms (necrotizing enterocolitis) AND (probiotics). Results: 11 randomized trials were included, totaling 2,887 patients, 1,431 in the probiotic group and 1,456 in the control group. There was a reduction in the incidence of NEC (NNT = 25), overall death (NNT = 34), and neonatal sepsis (NNT = 34) in the probiotic group compared to the control group. Patients that received probiotic supplementation had lower food reintroduction time (p < 0.001) and hospitalization time (p < 0.001) when compared to those not receiving probiotics. There was no difference in mortality caused by NEC. Conclusion: In premature newborns, the use of probiotics is effective as a prophylaxis for NEC and its complications. Resumo: Objetivo: Elucidar os benefícios do uso de probióticos na prevenção de enterocolite necrosante (ECN) e de suas complicações em recém-nascidos prematuros. Método: Revisão sistemática de ensaios clínicos randomizados, que incluiu pesquisas efetuadas em três bases de dados (MEDLINE, EMBASE e LILACS), utilizando a combinação dos termos (necrotizing enterocolitis) AND (probiotics). Resultados: Foram incluídos 11 ensaios clínicos randomizados, totalizando 2.887 pacien- tes, sendo 1.431 no grupo Probiótico e 1.456 no grupo Controle. Houve redução na incidência de ECN (NNT = 25), de morte global (NNT = 34) e sepse neonatal (NNT = 34) no grupo Probiótico em relação ao grupo Controle. Pacientes alimentados com suple- mentação de probióticos tiveram tempo de reintrodução alimentar (p < 0,001) e de hospitalização (p < 0,001) menor quando comparados aos que não receberam. Não houve diferença na mortalidade causada por ECN. Conclusão: Em recém-nascidos prematuros, o uso de probióticos é eficaz na profilaxia de ECN e de suas complicações. Keywords: Home oxygen therapy, Children, Oxygen, Palavras-chave: Enterocolite necrosante, Probióticos, Prematuros